Konsep Belajar menurut az-Zarnuji - Siswadi Siswadi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Learning concept which afforded by az-Zarnuji is complete with normative values, though there’s a lot expression about learning concept which having practical character. Therefore, az-Zarnuji concepts is exactly easy to understand and able to actualize in all different place and time. In modern day, when science and technology thrive so fast, moral value start to attenuate and replaced by immoral culture value. Learning concept that afforded by az-Zarnuji actually have very instituted and applied in almost every education institutes in Indonesia. This understanable, considering this learning concept have logical character, easy to apply, and also accepted by all student in education institute environment, especially Islamic education